Ho Chi Minh’s theory on colonial revolution - Quoc Thanh, Pham (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
In discovering the way for national salvation and the important role and importance of revolutionary theory on national liberation, Ho Chi Minh creatively developed the theory of colonial revolution in the new age. This theory is based on the creative and dialectical promotion of Vietnamese traditional values and common human values, Marxist-Leninist revolutionary theory, and his own experience obtained from his participation in revolutionary movements both in Vietnam and overseas. Ho Chi Minh constructed a theoretical system of colonial liberation appropriate to the conditions in Vietnam. Ho Chi Minh’s theory of colonial liberation is a complete theory in terms of direction, tasks, forces, revolutionary leadership and methods, and solidarity between the Vietnamese revolution and the world revolution. Ho Chi Minh’s theory of colonial revolution has become the foundational content of the Vietnamese revolutionary path in the struggle for independence and freedom. Received: 24th March 2017; Revised: 21th April 2017; Accepted 28th April 2017